Effects of hypotension and/or hypocapnia during sevoflurane anesthesia on perfusion and metabolites in the developing brain of piglets—a blinded randomized study. Issue 9 (27th June 2016) - Ringer, Simone K.; Ohlerth, Stefanie; Carrera, Inés; Mauch, Jacqueline; Spielmann, Nelly; Bettschart‐Wolfensberger, Regula; Weiss, Markus
Summary: Background: Hypotension (HT) and/or hypocapnia (HC) are frequent complications occurring during pediatric anesthesia and may cause cerebral injury in the developing brain. Aim: The aim of this study is to investigate the effects of HT and/or HC on perfusion and metabolism in the developing brain. Methods: Twenty‐eight piglets were randomly allocated to four groups: control (C), HT, HC, and hypotension and hyocapnia (HTC). Anesthesia was induced and maintained using sevoflurane. Fentanyl was added for instrumentation. Piglets were fully monitored and their lungs were artificially ventilated. Before treatment, conventional magnetic resonance imaging (MRI), dynamic susceptibility‐contrast‐enhanced T2*‐weighted MRI (DSC‐MRI), and single voxel proton MR spectroscopy ( 1 H MRS) were performed. Hypotension (mean arterial blood pressure: 30 ± 3 mmHg) was induced by blood withdrawal and nitroprusside infusion, and hyperventilation was used to induce HC (PaCO2 : 2.7–3.3 kPa). 1 H MRS and DSC‐MRI were repeated immediately once treatment goals were achieved and 120 min later. Radiologists were blinded to the groups. DSCI‐MRI and 1 H MRS analyses were performed in the thalamus, occipital and parietal lobe, hippocampus, and watershed areas. Results: In comparison to C, mean time to peak (TTP) increased with HTC in all brain areas as assessed with DSC‐MRI ( n = 26). Using 1 H MRS, a significant decrease in N ‐acetyl aspartate, choline, and myoinositol, as well as an increase in glutamine–glutamate complex (Glx) were detected independent of group. Compared to C, changes were more pronounced for Glx (due to an increase in glutamate) and myoinositol with HTC, for N ‐acetyl aspartate with HT, and for Glx with HC. No lactate signal was present. Conclusions: The combination of HT and HC during sevoflurane anesthesia resulted in alteration of cerebral perfusion with signs of neuronal dysfunction and early neuronal ischemia. HT and HC alone also resulted in signs of metabolic disturbances despite the absence of detectable cerebral perfusion alterations. Abstract :